Development, validation and feasibility of a Patient Satisfaction Questionnaire for evaluating the quality performance of a diagnostic small fibre neuropathy service: A qualitative study - Margot Geerts; Janneke G. J. Hoeijmakers; Brigitte A. B. Essers; Ingemar S. J. Merkies; Catharina G. Faber; Mariëlle E. J. B. Goossens (Wiley, 2024)
Abstract Introduction and Aim Small fibre neuropathy (SFN) is a peripheral neuropathy, leading to neuropathic pain and autonomic dysfunction. An evidence‐based standardized patient diagnostic SFN service has been implemented in the Netherlands for improving patient‐centred SFN care. However, the quality of care of this diagnostic SFN service has never been assessed from a patient perspective. The aim of this study was to develop and validate an SFN‐Patient Satisfaction Questionnaire (SFN‐PSQ) to measure the quality performance of a standardized diagnostic SFN service. Methods A descriptive qualitative study to create the SFN‐PSQ was performed using the (COREQ (Consolidated Criteria for Reporting Qualitative Research) checklist. For item generation and content development, domains and/or items from validated PSQs were selected. The content development and content validity were performed using a Delphi method with SFN expert caregivers with different backgrounds. By using the three‐step‐test method in individual cognitive interviews, the content validity by patients was finalized. Results In one online Delphi panel round, the content of the first concept of the SFN‐PSQ was validated, which resulted in the second concept of the SFN‐PSQ. From July 2019 till March 2020, nine patients consented to participate in the individual cognitive interviews. The most significant changes of the new questionnaire were adding domains and items concerning the waiting list, the diagnostic services and consultation by the hospital psychiatrist. Also, a differentiation was made for both an inpatient and outpatient diagnostic SFN service. Furthermore, the clarity and intelligibility of the domains/items were improved, resulting in an increased comprehension of the SFN‐PSQ. Ultimately, the new developed SFN‐PSQ consisted of 10 domains and 51 items, suitable for measuring patient satisfaction of the neurological analysis in patients with SFN. Conclusion Through item generation, expert opinions and interviews with patients, the SFN‐PSQ was developed and validated, and feasibility was confirmed. The structure of the questionnaire, based on the logistic and diagnostic SFN pathway, could be used as a model in other hospitals to improve the quality, continuity and access of SFN care and other chronic diseases taking into account potential cross‐cultural differences. Patient or Public Contribution Caregivers were involved in the item generation and content development of the questionnaire. Patients were directly involved in testing the content validity and feasibility of the SFN‐PSQ. Clinical Trial Registration Not applicable.